Analisis faktor penghambat motivasi berhenti merokok berdasarkan Health Belief Model pada mahasiswa Fakultas Teknik Universitas Brawijaya Malang - Kumboyono (Jurnal Keperawatan Soedirman, 2011)
Cigarette is one of the most dangerous killers, because it has potentially effect to cause various diseases, not only on smokers but also passive smokers. Therefore, smokers should have a strong motivation to quit smoking. The active smokers in Engineering Faculty student’s of Brawijaya University largely been experiencing psychological addiction to smoking and have low desire to quit smoking. This study aimed to identify factors that inhibiting student’s motivation to quit smoking in Engineering Faculty of Brawijaya University Malang. This research uses cross sectional design. Samples are selected by using purposive sampling with exclusion and inclusion criteria, then obtained samples were 96 people. The variables in this research were perceived of threat to diseases caused by smoking, perceived benefits to quit smoking, perceived barrier to quit smoking, and motivation to quit smoking. The results showed only 12,5% respondent who have high motivation to quit smoking. Whereas the factors that can inhibit respondent’s motivation to quit smoking were perceived of threat to diseases caused by smoking (p = 0.001), perceived benefits to quit smoking (p = 0.003), perceived barrier to quit smoking (p = 0.000). The conclusion of this research were miss perception about threat to diseases caused by smoking, perceived benefits to quit smoking, perceived barrier to quit smoking can inhibit smoker’s motivation to quit smoking